Hospitality management and digital transformation : balancing efficiency, agility and guest experience in the era of disruption - Busulwa, Richard, 1980-; Evans, Nina; Oh, Aaron; Kang, Moon (Oxon ; New York : Routledge, 2021)
Hospitality managers are at a critical inflection point. Digital technology advancements are ramping up guest expectations and introducing nontraditional competitors that are beginning to disrupt the whole industry. The hospitality managers whose organizations are to thrive need to get their organizations into a position where they can effectively leverage digital technologies to simultaneously deliver breakthroughs in efficiency, agility, and guest experience. Hospitality Management and Digital Transformation is a much-needed guidebook to digital disruption and transformation for current and prospective hospitality and leisure managers. The book: Explains digital technology advancements, how they cause disruption, and the implications of this disruption for hospitality and leisure organizations. Explains the digital business and digital transformation imperative for hospitality and leisure organizations. Discusses the different digital capabilities required to effectively compete as a digital business. Discusses the new and/or enhanced roles hospitality and leisure managers need to play in effecting the different digital capabilities, as well as the competencies required to play these roles. Discusses how hospitality and leisure managers can keep up with digital technology advancements. Unpacks more than 36 key digital technology advancements, discussing what they are, how they work, and how they can be implemented across the hospitality and leisure industry. This book will be useful for advanced undergraduate and postgraduate students studying strategic management, IT, information systems, or digital business-related courses as part of degrees in hospitality and leisure management; as well as practitioners studying for professional qualifications.
OCLC-licensed vendor bibliographic record.
Keywords: Hospitality industry -- Management; Hospitality; Strategic planning; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism; BUSINESS & ECONOMICS / E-Commerce / General (see also COMPUTERS / Electronic Commerce)